Molecular Epidemiology of and Risk Factors for Extensively Drug-Resistant Klebsiella pneumoniae Infections in Southwestern China: A Retrospective Study - Tian, Xiaolang; Huang, Changwu; Ye, Xiaoli; Jiang, Hongyan; Zhang, Rufang; Hu, Xiaofang; Xu, Dongshuang (Frontiers in Pharmacology, 2019)
Background: The increasing prevalence of extensively drug-resistant Klebsiella pneumoniae (XDR-KP) poses a serious threat to clinical anti-infective treatment. This retrospective study assessed the molecular epidemiology of and risk factors for infections with XDR-KP to investigate the mechanism of drug resistance and the epidemiological characteristics. Methods: A retrospective 1:2 case-control study was conducted at Chongqing Renji Affiliated Hospital of the Chinese Academy of Sciences University from January 2015 to December 2017. A total of 69 non-repetitive XDR-KP strains were collected. Patients infected with XDR-KP comprised the case group, and 138 matched patients with non-XDR-KP infection at the same site comprised the control group. The chi-square test and logistic regression were performed to evaluate the related risk factors. Molecular typing was performed by multilocus sequence typing (MLST). Potential resistance genes were detected by polymerase chain reaction (PCR) and sequencing. Predictors of 28-day mortality in patients with XDR-KP infection were also identified in our study. Results: Only tegacycline and polymyxin B showed favourable in vitro drug sensitivity tests. These XDR-KP strains had a high prevalence rate (n=66, 95.7%) of carbapenemase-related drug resistance genes. Among them, KPC-2 was the most frequently detected gene (n=52, 75.4%). Particularly, all of the isolates harboured multiple drug resistance genes. Epidemiological analysis showed that fifty-eight XDR-KP isolates were resistant strains with the ST-11 genotype. Multivariate logistic regression analysis showed that ICU admission (OR: 3.28, 95% CI: 1.66-6.49, P<0.001), tracheal cannula (OR: 3.16, 95% CI: 1.48-6.76, P=0.003), and carbapenem exposure (OR: 3.16, 95% CI: 1.25-7.98, P=0.015) were independent risk factors for XDR-KP infection. Solid tumours (OR: 7.22, 95% CI: 1.84-28.34, P=0.005) and septic shock (OR: 9.46, 95% CI: 2.00-44.72, P=0.005) were independent risk factors for 28-day mortality from XDR-KP infection. Conclusion: This study showed that XDR-KP isolates were highly resistant and exhibited clonal transmission. ST11 was the predominant epidemic type of XDR-KP producing KPC-2 in Southwestern China. Physicians should be aware of these high-risk patients with notable predictive factors for XDR-KP infection. More importantly, strengthening the surveillance of patients with cancer and septic shock is important for reducing the mortality rate of XDR-KP infection.